1995
DOI: 10.1111/j.1460-9592.1995.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of bone marrow transplant recipients less than two years of age

Abstract: The charts and anaesthetic records of 97 infants less than two years of age who underwent bone marrow transplantation at the University of Minnesota from 1978-1992 were retrospectively reviewed. These infants underwent 564 general anaesthetics. There were 48 perioperative complications, most (39) involving the airway. There were 20 difficult intubations occurring in 13 patients. The causes of the difficult intubations were anatomical abnormalities (12), mucositis (4), pharyngeal oedema (3) and emesis upon indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 9 These factors, when combined with the pulmonary sequelae frequently seen in BMT patients, put children at greater risk of airway compromise than adults. Beebe et al 10 described the anesthetic management of 97 pediatric BMT patients younger than 2 years of age, and the reasons for difficult intubations. The authors found that mucositis and anatomical abnormalities made intubation difficult in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 These factors, when combined with the pulmonary sequelae frequently seen in BMT patients, put children at greater risk of airway compromise than adults. Beebe et al 10 described the anesthetic management of 97 pediatric BMT patients younger than 2 years of age, and the reasons for difficult intubations. The authors found that mucositis and anatomical abnormalities made intubation difficult in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Before HSCT, patients receive anesthesia for procedures such as permanent central venous catheter placement, bone marrow aspiration, tracheostomy, and total body irradiation. Afterward, there are bone marrow biopsies to determine the success of HSCT and monitor for the development of graft‐versus‐host disease, radiological studies, and treatment of any surgical complications that arise (9). Although MIOP has adverse implications for anesthetic management (10), the literature describing the anesthetic management of MIOP patients is limited.…”
Section: Introductionmentioning
confidence: 99%